2020
DOI: 10.1016/j.fsisyn.2020.06.003
|View full text |Cite
|
Sign up to set email alerts
|

The effect of contextual information on decision-making in forensic toxicology

Abstract: The impact of cognitive bias on decisions in forensic science has been demonstrated in numerous disciplines such as DNA and fingerprints, but has not been empirically investigated in the more objective domains, such as forensic toxicology. In the first experiment, participants (n = 58) were affected by irrelevant case information when analysing data from an immunoassay test for opiate-type drugs. In the second experiment, participants (n = 53) were biased in their choice of tests, for example, the age of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Importantly, contextual information can shape not only an examiner's conclusion but also the process by which they reach that conclusion (Dror, 2009;Kukucka, 2014). For example, Hamnett and Dror (2020) recently found that forensic toxicology trainees who read an irrelevant case history prior to testing for the presence of opiates opted to perform different tests than those who did not. Future work should continue to examine the mechanism(s) by which context affects forensic judgments.…”
Section: Ontextual Inform Ationmentioning
confidence: 99%
“…Importantly, contextual information can shape not only an examiner's conclusion but also the process by which they reach that conclusion (Dror, 2009;Kukucka, 2014). For example, Hamnett and Dror (2020) recently found that forensic toxicology trainees who read an irrelevant case history prior to testing for the presence of opiates opted to perform different tests than those who did not. Future work should continue to examine the mechanism(s) by which context affects forensic judgments.…”
Section: Ontextual Inform Ationmentioning
confidence: 99%
“…Furthermore, the LR and the underlying Bayesian logic are adequate, and therefore should be the prescriptive model for logically updating beliefs about the evidence provided (Dawid, 2002; Good, 1989a, 1989b; Hahn, 2014). This formalization cannot, however, embrace all the scientific and cognitive challenges raised by traces retrieved from a singular, non‐reproducible, generally unobserved past (Dror, 2017; Dror & Pierce, 2020; Gardner et al, 2019; Hamnett & Dror, 2020): a trace is typically only a specimen (it is usually unwillingly generated, and its representativeness arises from an intentional, specific, singular choice made by the crime scene officer) and not a sample (random selection, controlled within a homogeneous population), as one cannot know the whole population of existing traces created through the event of interest. It is often partial, incomplete, mixed, contaminated.…”
Section: Reflections On Scientific Opinionmentioning
confidence: 99%
“…Furthermore, the LR and the underlying Bayesian logic are adequate, and therefore should be the prescriptive model for logically updating beliefs about the evidence provided (Dawid, 2002;Good, 1989aGood, , 1989bHahn, 2014). This formalization cannot, however, embrace all the scientific and cognitive challenges raised by traces retrieved from a singular, non-reproducible, generally unobserved past (Dror, 2017;Dror & Pierce, 2020;Gardner et al, 2019;Hamnett & Dror, 2020):…”
mentioning
confidence: 99%
“…From this studies, there are "contradictions" in the influence of existing contextual information on the decision-making of the examiners. Some research shows the task-irrelevant information causing the examiner's decision-making bias and dispersion [9][10][11], while the other shows no effect, which means the extraneous information does not have significant effect on the judgment of the examiners [12][13]. The different results of these literatures may be attributed to the various types of contextual information provided in these studies, for example, superior's power, flaws in experimental design, and opinions of senior experts may lead to potential biases.…”
mentioning
confidence: 99%
“…Two experiments on forensic toxicology and cognitive bias were conducted by Hamnett et al [11]. The first experiment studied the effect of irrelevant case information, such as whether the deceased had drug intake, morphine treatment, etc., on participants' analysis data from opiate-type drugs.…”
mentioning
confidence: 99%